MARKET BASKET ANALYSIS METHOD ON SALES DATA USING FP-GROWTH ALGORITHM - Marcelino Irawan, Kenny; Tri Wulansari, Tina; Wanti Wulan Sari, Nariza (Universitas Mulia, 2021)
Product promotion is a way for business owners to increase sales of existing goods. Business owners could use association rules as a consideration of product promotion policies. Determination of association rules can be determined using the market basket analysis method with the fp-growth algorithm. From the research, there are 248 association rules for goods that are often purchased simultaneously with minimum support of 0.01 and minimum confidence of 0.1. Of the 248 rules, there are seven rules that have a confidence value of more than 0.5. Of the seven rules, flour appeared five times, and the cake mat and cake box had the highest confidence value of 0.62 and a lift of 5.54. Therefore, we recommend shop owners to place wheat flour on the main display close to items often purchased together, such as sweetened condensed milk, sugar, powdered margarine, and margarine. In addition, shop owners can also promote bundling cake boxes and cake mats.